Women and media: A critical introduction - Byerly, Carolyn M.; Ross, Karen (John Wiley & Sons, 2008)
Women and Media is a thoughtful cross-cultural examination of the ways in which women have worked inside and outside mainstream media organizations since the 1970s. Rooted in a series of interviews with women media workers and activists collected specifically for this book, the text provides an original insight into women’s experiences. Explains the ways that women have organized their internal and external campaigns to improve media content (or working conditions) for women, and established womenowned media to gain a public voice. Identifies key issues and developments in feminist media critiques and interventions over the last 30 years, as these relate to production, representation and consumption. Functions as both a research case study and a teaching text.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; cinéma; communication; discipline; histoire et politique; médias; projet charge mentale; périodes historiques; ressource en ligne; thématiques; travail